2019
DOI: 10.3390/electronics8121469
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic-Discharge-Immunity Impacts in 300 V nLDMOS by Comprehensive Drift-Region Engineering

Abstract: Electrostatic discharge (ESD) events are the main factors impacting the reliability of Integrated circuits (ICs); therefore, the ESD immunity level of these ICs is an important index. This paper focuses on comprehensive drift-region engineering for ultra-high-voltage (UHV) circular n-channel lateral diffusion metal-oxide-semiconductor transistor (nLDMOS) devices used to investigate impacts on ESD ability. Under the condition of fixed layout area, there are four kinds of modulation in the drift region. First, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Lin et al reported "Electrostatic-Discharge-Immunity Impacts in 300 V nLDMOS by Comprehensive Drift-Region Engineering" [6]. This paper focuses on comprehensive drift-region engineering for ultra-high-voltage (UHV) circular n-channel lateral diffusion metal-oxide-semiconductor transistor (nLDMOS) devices used to investigate impacts on ESD ability.…”
Section: The Topics Of Intelligent Electronic Device and Its Applicatmentioning
confidence: 99%
“…Lin et al reported "Electrostatic-Discharge-Immunity Impacts in 300 V nLDMOS by Comprehensive Drift-Region Engineering" [6]. This paper focuses on comprehensive drift-region engineering for ultra-high-voltage (UHV) circular n-channel lateral diffusion metal-oxide-semiconductor transistor (nLDMOS) devices used to investigate impacts on ESD ability.…”
Section: The Topics Of Intelligent Electronic Device and Its Applicatmentioning
confidence: 99%